Pengaruh Mindfullnes spiritual dengan metode STOP terhadap kemandirian fisik pasien TB Paru di Kabupaten Sikka - Donatus Korbianus Sadipun; Yohanes Paulus Pati Rangga (Jurnal Ilmiah Wahana Pendidikan, 2021)
The research was to analyze the influence of mindfulness spiritual therapy with the STOP (Stop-take a breath-observe the present-proceed with a smile) method the physical self-reliance of patients with pulmonary tuberculosis. Method: This research used quasi-experimental non equivalen with control group design. This research was to conducted in 4 comunity health centers. The sample was 54 respondents divided in 2 groups with 27 responden per group taken by using Purposive sampling teqnique. The intervention was mindfulness spiritual therapy using STOP Method for 5 weeks. Mandiri health card was used as the instrument of the study. In analyzing the data, the researcher used wilcoxon sign rank test Results: the study showed that intervention groups (p 0,000) and control groups (p 0,366). there is an influence of the intervention group than the control groups. Conclusion: Therefore, it can be concluded that Mindfulness Spiritual Therapy using STOP method could increase the physical self-reliance of patients with pulmonary tuberculosis.